Analisis Persepsi Mahasiswa Universitas Islam Riau Terhadap Kelayakan Konversi BPR Unisritama Menjadi BPR Syariah: Analisis Persepsi Mahasiswa Universitas Islam Riau Terhadap Kelayakan Konversi BPR Unisritama Menjadi BPR Syariah - Hendra Eka Saputra hendra (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2021)
The background of this research is that bank is a forum for financial activity. Banks are included in the category of a benchmark for a country in improving the economy. The formulation of the research problem is how the perception of Riau Islamic University students on the feasibility of converting the Unisritama Rural Bank (BPR) into a Sharia Rural Bank (BPRS)? The purpose of this study was to determine the perceptions of Riau Islamic University students on the feasibility of converting Unisritama People's Credit Bank (BPR) into a Sharia People's Financing Bank (BPRS). : intensity, size, repetition, movement and novelty. factors within a person that influence the perception selection process include: understanding (learning), motivation, and personality. The methodology used in this research is descriptive method. The sample taken by the whole population is 100 people. The sampling technique is to use the Slovin formula. Based on the results of research on the analysis of the perceptions of Riau Islamic University students on the feasibility of converting the people's credit bank Unisritama into a sharia people's finance bank processed through the respondents' answers, it can be concluded that P = 81.21% which means the analysis of the perceptions of Riau Islamic University students on the feasibility of converting people's credit banks. Unisritama being a sharia people's finance bank answered